Writing for the (virtual) other: Bakhtinian intertextuality within online L2 writing exchanges. Issue 1 (1st January 2019) - Strickland, Brandee Marie
ABSTRACT: In this article, I explore practical implications of the theories of language of M.M. Bakhtin within university second language writing classrooms. Specifically, I examine the presence of Bakhtinian intertextuality within online intercultural exchanges involving the use of Computer-Mediated Communication (CMC) technology. I describe a CMC exchange between university students in Canada enrolled in Spanish classes and Chilean university students of English. The students communicated using a bilingual blog, Skype, Facebook and Dropbox to meet, share their writing and engage in peer review. The data analysed include the students' writings in English and Spanish in the blog, drafts of student essays and student comments in final interviews. Drawing on Bakhtin's theories, I used a qualitative approach to analyse the data, identifying instances of intertextuality across the students' writing. Based on my findings, I suggest that the online exchange offered positive conditions for the sharing of language, which led to contextualised learning of new lexical items and the creation of intertextually richer student writing in the L2.